Nucleases in homologous recombination as targets for cancer therapy - Bartosova, Zdenka; Krejci, Lumir (FEBS letters, 2014)
Genomic DNA is constantly challenged from endogenous as well as exogenous sources. The DNA damage response (DDR) mechanism has evolved to combat these challenges and ensure genomic integrity. In this review, we will focus on repair of DNA double-strand breaks (DSB) by homologous recombination and the role of several nucleases and other recombination factors as suitable targets for cancer therapy. Their inactivation as well as overexpression have been shown to sensitize cancer cells by increasing toxicity to DNA-damaging agents and radiation or to be responsible for resistance of cancer cells. These factors can also be used in targeted cancer therapy by taking advantage of specific genetic abnormalities of cancer cells that are not present in normal cells and that result in cancer cell lethality.
Keywords: Genomic integrity; cílená molekulární terapie; Neoplasms; Homologous recombination; Homologous Recombination; Inhibitor; Recombinational DNA Repair; inhibitory enzymů; Deoxyribonucleases; Enzyme Inhibitors; rekombinační oprava DNA; homologní rekombinace; Cancer therapy; Animals; lidé; enzymy opravy DNA; Humans; zvířata; deoxyribonukleasy; Molecular Targeted Therapy; nádory; Nuclease; DNA Repair Enzymes